Research on Productivity Evaluation Method Based on Shale Gas Well Early Flow Stage Data - Yize Huang; Xizhe Li; Wei Guo; Xiaohua Liu; Wei Lin; Chao Qian; Mengfei Zhou; Yue Cui; Xiaomin Shi (Geofluids)
Since the accurate early gas well production regime is related to the production period and final productivity, it is crucial to make better use of early flow stage production data for gas well productivity evaluation. Absolute open flow potential (AOF) and estimated ultimate recovery (EUR) are essential parameters for evaluating the productivity of shale gas wells. This study establishes new AOF calculation methods for the early production stage. The analytical model can calculate the AOF only by using stable pressure and production data in the flowback stage, which greatly improves the efficiency of productivity evaluation. Three methods have, respectively, calculated the productivity of the shale gas wells above 3500 m in the Luzhou block. The results show that well L2-3 has the highest AOF, averaging 278.1×104 m3/d, whereas well Y2-8 has the lowest AOF, averaging 100.2×104 m3/d. Different AOF calculation methods are identified for gas wells in different stages of production. For gas wells in the initial unstable flow stage, a pseudogas production index method is recommended. A water production index analysis method, with lower evaluation results, is proposed for gas wells in the flowback stage. A modern production decline analysis method is found to be preferred for calculating the EUR of deep shale gas wells. Well L2-3 has the highest average EUR of 1.26×108 m3, whereas well Y2-8 has the lowest average EUR of 0.42×108 m3. The Blasingame method is recommended for medium-to-high-production gas wells, whereas a normalized pressure integral method is suggested for low-production wells. A strong exponential quantitative link between the AOF and the EUR shows that a fracture system’s initial productivity has a significant impact on a well’s EUR. The findings of this study enrich the productivity evaluation system, increase the accuracy of productivity evaluation results, and provide theoretical support for deep shale gas wells.